ANALISIS PERBANDINGAN METODE MKJI 1997 DENGAN PKJI 2023 DALAM MENENTUKAN NILAI KAPASITAS JALAN PADA JALAN PERKOTAAN (STUDI KASUS: JL. DOKTOR MANSYUR) - Br Tarigan, Pagit Juni Sartika; Sianturi, Fenny Novita Meysabed; Silalahi, Oktavia Ully Artha; Badriansyah, Dine Noviandri (RETENSI, 2025)
Road capacity is one of the things needed in the process of determining the level of road service. There are several data needed in the process of determining road capacity using both the MKJI 1997 and PKJI 2023 methods. These data are road width data, median conditions, shoulder width data, curb data, population data, number of vehicles crossing the road, and side friction data. All of this data can be obtained by conducting a direct survey at the review location. The review location is an urban road (Jl. Doktor Mansyur), Medan City, North Sumatra. In addition, vehicle types are also grouped because they will have an impact on the road section capacity value. Traffic volume and side friction surveys are carried out on weekdays and weekend. With the acquisition of road capacity values, the level of road service can be determined to be followed up if the road service level is no longer working according to the function of the road. After conducting a traffic survey and data processing, the road service level was obtained in category F due to very high side frictionconditions and dense activity on the road section.